Efeito neuroreparador do ácido decanoico em modelo animal de isquemia cerebral - Nunes, Antonio Ítalo dos Santos (2024)
Cerebral ischemia is a neurological disorder that occurs due to the abrupt interruption of blood flow in the brain and can result in cognitive and motor impairments. Decanoic acid has been proposed as a potential therapeutic agent in neurological diseases as it blocks AMPA receptors and acts on neuroinflammation. In this context, the aim of this study was to investigate the effect of decanoic acid in a model of cerebral ischemia by middle cerebral artery occlusion (MCAO) in mice. For this purpose, mice received different doses of decanoic acid (62.5, 125, 250, 500, and 1000 mg/kg) or vehicle by gavage for 7 or 14 days after the induction of ischemia. Morphological analysis of the ischemic area was performed by TTC staining. Motor asymmetry, postural tone, spatial and contextual memory deficits were also evaluated using the Cylinder, Limb Clasping, OLT, and NORT tests, respectively. Furthermore, investigations of the mechanisms involved in this neurorepair were carried out by ELISA technique for inflammatory biomarkers and Western Blot to analyze AMPA receptor pathways and autophagy. The results showed that, after 7 and 14 days of treatment, decanoic acid was able to promote neurorepair effects, evidenced by the reduction of the ischemic area and improvement in motor, cognitive, and memory impairments. In addition to revealing anti-inflammatory effects, reducing the expression of pro-inflammatory cytokines, and surprisingly, this effect seems not to be related to changes in the expression of AMPA receptors or the autophagy pathway. This study suggests that decanoic acid has therapeutic potential for ischemic injuries, promoting functional and cognitive recovery, as well as acting on reducing inflammation.